MiRNA dysregulation is an emerging modulator of genomic instability. (November 2021) - Ferragut Cardoso, Ana P.; Banerjee, Mayukh; Nail, Alexandra N.; Lykoudi, Angeliki; States, J. Christopher
Abstract: Genomic instability consists of a range of genetic alterations within the genome that contributes to tumor heterogeneity and drug resistance. It is a well-established characteristic of most cancer cells. Genome instability induction results from defects in DNA damage surveillance mechanisms, mitotic checkpoints and DNA repair machinery. Accumulation of genetic alterations ultimately sets cells towards malignant transformation. Recent studies suggest that miRNAs are key players in mediating genome instability. miRNAs are a class of small RNAs expressed in most somatic tissues and are part of the epigenome. Importantly, in many cancers, miRNA expression is dysregulated. Consequently, this review examines the role of miRNA dysregulation as a causal step for induction of genome instability and subsequent carcinogenesis. We focus specifically on mechanistic studies assessing miRNA(s) and specific subtypes of genome instability or known modes of genome instability. In addition, we provide insight on the existing knowledge gaps within the field and possible ways to address them.